ANALYSIS OF FILING UNIT WORKLOAD USING ABK-Kes METHOD AT MITRA SEHAT SITUBONDO HOSPITAL - Ikawati, Fita Rusdian; Bulgis, Malikal; Nabor, Wihelmina Tista (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
The implementation of medical records management requires competent and professional human resources, as well as appropriate workload allocation. Mitra Sehat Situbondo Hospital currently employs two filing officers: one with a bachelor's degree in education and the other with a high school background. The research aims to analyze the workload of these officers and determine the staffing requirements for the filing unit. This descriptive qualitative research utilizes data collection methods such as interviews and observations.According to the findings, the calculations using ABK Kes indicate a requirement for five healthcare human resources, highlighting a need for an additional three employees in the filing unit.In summary, the research underscores the importance of adequately staffing the medical records management team to ensure efficient operations and effective patient care at Mitra Sehat Situbondo Hospital.